Effect of compression stockings on venous blood velocity and blood flow - Stein, Paul D.; Matta, Fadi; Yaekoub, Abdo Y.; Ahsan, Syed T.; Badshah, Aaref; Younas, Fahad; Denier, James E. (Thrombosis and Haemostasis, 2010)
The effects of graduated compression stockings (GCS) on venous blood velocity have not been established. In healthy subjects, most investigations showed no effect on blood velocity, but mixed results have been reported. In this investigation we to test the hypothesis that popliteal blood velocity is increased by properly fitted GCS. Time average peak velocity in the popliteal vein, as well as time average mean velocity, vein diameter and mean volumetric flow were measured by pulsed wave Doppler ultrasound in 25 healthy male volunteers without compression stockings and repeated with fitted thigh-length compression stockings. Measurements were obtained while supine and while sitting at rest and during ankle exercise. Thigh-length GCS did not increase popliteal vein blood velocity, diameter, or volumetric blood flow while supine or sitting, with or without ankle exercise.
Keywords: Venous blood velocity; deep venous thrombosis; pulmonary embolism; graduated compression stockings